Methodology of Integration for Competitive Technical Intelligence with Blue Ocean Strategy: Application to an exotic fruit - Marisela Rodríguez Salvador; Manuel Alejandro Bautista Reyes (Journal of Intelligence Studies in Business)
This article presents a new methodology that integrates Competitive Technical Intelligence with Blue Ocean Strategy. We explore new business niches taking advantage of the synergy that both areas offer, developing a model based on cyclic interactions through a process developed in two stages: Understanding opportunity that arise from idea formulation to decision making and strategic development. The validity of our approach (first stage) was observed in the evaluation of an exotic fruit, Anacardium Occidentale, in the South of the State of Veracruz, Mexico with the support of the university ITESM, Campus Monterrey. We identified critical factors for success, opportunities and threats. Results confirm the attractiveness of this crop.